EVALUASI PRODUKTIFITAS DAN KUALITAS BEBERAPA VARETAS KACANG TANAH (Arachis hypogaea L.) DI TANAH BERTEKSTUR LIAT - Mona Faronika1 Mona Faronika1; Luthfi Aziz Mahmud Siregar; Hasmawi Hasyim2 Hasmawi Hasyim2 (Universitas Sumatera Utara, 2013)
Peanut is the second legums largest planted in Indonesia after soybean. It needed soil with sand to silt loam. Clay Texture of Soil has capability to defend water and soil minerals, but low infiltration rate, organic substances and Nitrogen, also big cracked in dry season because particle clay of soil was shrink. The aim of the research is to get peanut with high yield and best quality at Clay Texture of Soil. The experiment conducted at BBI Palawija Tanjung Selamat, Deli Serdang (± 57 meters above sea level) from April to July 2012. The experiment used Randomized Block Design with variety treatment that consists of six varieties : Gajah, Jepara, Biawak, Landak, Komodo and Simpai, with four replications. The data was analyzed by Analysis of Variance and continued with Duncan’s Multiple Range Test. Varieties showed significantly different on plant height 2-9 weeks after planted, time of flower initiation, total pods per plant, total pops, total pod producing seed, number of seed per plant, number of seed per plot, 100 seed weight, seed weight per plant, and percentage of peds producing pod. Variety were not significantly different on number of branch 9 weeks after planted, total peds, percentage pods producing seed, total seed per pod, total pod per plot, number of seed per plot, seed weight per plot, dry weight of shoot, dry weight of root and grow plant percentage. Qualities observation of seed were watched colour, size and protein degree. Keyword : variety, peanut, soil teksture